Pathway engineering for high-yield production of lutein in Escherichia coli. Issue 1 (15th May 2021) - Takemura, Miho; Kubo, Akiko; Watanabe, Asuka; Sakuno, Hanayo; Minobe, Yuka; Sahara, Takehiko; Murata, Masahiro; Araki, Michihiro; Harada, Hisashi; Terada, Yoshinobu; Yaoi, Katsuro; Ohdan, Kohji; et al.
Abstract: Lutein is an industrially important carotenoid pigment, which is essential for photoprotection and photosynthesis in plants. Lutein is crucial for maintaining human health due to its protective ability from ocular diseases. However, its pathway engineering research has scarcely been performed for microbial production using heterologous hosts, such as Escherichia coli, since the engineering of multiple genes is required. These genes, which include tricky key carotenoid biosynthesis genes typically derived from plants, encode two sorts of cyclases (lycopene ε- and β-cyclase) and cytochrome P450 CYP97C. In this study, upstream genes effective for the increase in carotenoid amounts, such as isopentenyl diphosphate isomerase ( IDI ) gene, were integrated into the E. coli JM101 (DE3) genome. The most efficient set of the key genes ( MpLCYe, MpLCYb and MpCYP97C ) was selected from among the corresponding genes derived from various plant (or bacterial) species using E. coli that had accumulated carotenoid substrates. Furthermore, to optimize the production of lutein in E. coli, we introduced several sorts of plasmids that contained some of the multiple genes into the genome-inserted strain and compared lutein productivity. Finally, we achieved 11 mg/l as lutein yield using a mini jar. Here, the high-yield production of lutein was successfully performed using E. coli through approaches of pathway engineering. The findings obtained here should be a base reference for substantial lutein production with microorganisms in the future.